2009
DOI: 10.1590/s0103-64402009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of root canal filling materials for primary teeth: zinc oxide and eugenol cement, Calen paste thickened with zinc oxide, Sealapex and EndoREZ

Abstract: This study evaluated in vitro the antibacterial activity of 4 root canal filling materials for primary teeth -zinc oxide and eugenol cement (ZOE), Calen paste thickened with zinc oxide (Calen/ZO), Sealapex sealer and EndoREZ sealer -against 5 bacterial strains commonly found in endodontic infections (Kocuria rhizophila, Enterococcus faecalis, Streptococcus mutans, Escherichia coli and Staphylococcus aureus) using the agar diffusion test (agar-well technique). Calen paste, 1% chlorhexidine digluconate (CHX) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 17 publications
(11 reference statements)
3
49
0
5
Order By: Relevance
“…In spite of presenting high antimicrobial activity (12), it appear to be no published reports investigating the biocompatibility of the Calen paste thickened with zinc oxide. The lack of peer-reviewed scientific data hinders a reliable comparison between the outcomes of this work and those of the previous researches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of presenting high antimicrobial activity (12), it appear to be no published reports investigating the biocompatibility of the Calen paste thickened with zinc oxide. The lack of peer-reviewed scientific data hinders a reliable comparison between the outcomes of this work and those of the previous researches.…”
Section: Discussionmentioning
confidence: 99%
“…Among the beneficial properties of calcium hydroxide are its biocompatibility (10,11), antibacterial activity (12), induction of mineralized tissue formation (13)(14)(15), activation of alkaline phosphatase and collagen synthesis (16) and ability to produce hydrolysis of bacterial endotoxin (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest success rate of ZOE paste in this study can be attributed to the fact that ZO powder has no significant antibacterial properties, due to lack of acidity and lack of release of antibacterial agents, which was reported by Daugela et al 20 Also, Alexandra et al reported least antibacterial activity of ZOE in an in vitro study comparing the antibacterial activity of four root canal filling materials for primary teeth. 21 Iodoform is another material, which is commonly used in root canals of primary teeth. It is used either in pure form or is combined with other materials like ZOE and calcium hydroxide.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is impossible to completely eradicate all microbes from root canal system as bacteria can obstinate in areas such as lateral canals, dentinal tubules and apical ramifications [6]. Consequently, the use of root canal filling materials with anti-microbial activity is considered beneficial in an effort to further reduce the number of remaining microorganisms and to eradicate the infection [7,8].…”
Section: Introductionmentioning
confidence: 99%